2015
DOI: 10.1016/j.jprot.2015.07.006
|View full text |Cite
|
Sign up to set email alerts
|

ProteinInferencer: Confident protein identification and multiple experiment comparison for large scale proteomics projects

Abstract: Shotgun proteomics generates valuable information from large-scale and target protein characterizations, including protein expression, protein quantification, protein post-translational modifications (PTMs), protein localization, and protein-protein interactions. Typically, peptides derived from proteolytic digestion, rather than intact proteins, are analyzed by mass spectrometers because peptides are more readily separated, ionized and fragmented. The amino acid sequences of peptides can be interpreted by mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 29 publications
(37 reference statements)
0
20
0
Order By: Relevance
“…1Bii). Although routinely only proteins identified by at least two peptides are reported in many studies, proteins identified using only one peptide using a stringent peptide-spectrum match (PSM) false discovery rate (FDR) can be informative [45, 46], especially when combined with specific transcript data [2, 3]. There was a good correlation between the protein groups identified using the Ae.…”
Section: Resultsmentioning
confidence: 99%
“…1Bii). Although routinely only proteins identified by at least two peptides are reported in many studies, proteins identified using only one peptide using a stringent peptide-spectrum match (PSM) false discovery rate (FDR) can be informative [45, 46], especially when combined with specific transcript data [2, 3]. There was a good correlation between the protein groups identified using the Ae.…”
Section: Resultsmentioning
confidence: 99%
“…An experiment-wide protein ranking value was computed as the sum of all discriminant function scores for all peptide-spectral matches made for each protein. 78 Target and decoy proteins were ranked from highest to lowest scores, and target and decoy scores were used to compute protein q- scores. 79 Final protein identifications were reported at protein FDR of 0.01.…”
Section: Methodsmentioning
confidence: 99%
“…The resulting peptide mixture is subjected to liquid chromatography coupled to tandem mass spectrometry (LC-MS/MS) analysis. Proteins are identified from the LC-MS/MS data by comparing the peptide fragment spectra against in-silico fragment spectra generated from a protein database [4]. As a rule of thumb, a protein is claimed to be identified, if at least two unique peptides are identified representing parts of the sequence.…”
Section: Analysis Of Proteoforms: Challengesmentioning
confidence: 99%